First record of the black twig borer, Xylosandrus compactus (Coleoptera: Curculionidae, Scolytinae) in Spain - Leza, Mar; Nuñez, Luis; Riba, Josep Maria; Comparini, Claudia; Roca, Álvaro; Gallego, Diego (Zootaxa, 2020)
We present the first record for Spain of the black twig borer, Xylosandrus compactus, an ambrosia beetle of Asian origin, collected from an infested carob tree located in Calvià (Majorca, Balearic Islands, Spain). X. compactus is included in the EPPO Alert List, and it has been recently reported causing damages in a Mediterranean maquis ecosystem in Italy and Southern France. Here, we discuss about the first steps of management of this Invasive Alien species (IAS), the eradication plan and the hypothesis of the path of introduction in this Western Mediterranean island.